Reducing Cadmium in Cocoa (Theobroma cacao) Cultivars: Analysis of Advantages and Limitations of Different Strategies and Their Potential Application in Colombia - Claudia Lucumí Villegas; Nathali Jiménez Quiroga; Andrés Dávalos; Camila Pizano (International Journal of Agronomy)
The large global demand for cocoa positions this fruit as an agrifood product of great economic value, with high-quality standards regarding its sensory and nutritional characteristics. Entities such as the Pollutants Panel of the European Food Safety Authority (EFSA) and the European Union (EU) have strictly regulated cadmium (Cd) content in cocoa-based products and derivatives. Consequently, cocoa exports in countries such as Colombia could be threatened due to the high concentrations of Cd present in its soils. Therefore, there is a clear need for developing techniques that reduce Cd in the beans and in soils. This review analyzes two strategies utilized for its mitigation: (i) the selection of varieties by genotype (pure and hybrid cocoa) according to differences in their absorption, accumulation, and Cd translocation and (ii) the use of organic amendments such as biochar in soils. Studies have found significant differences in the uptake, accumulation, and translocation of Cd across cultivars. Although exclusively using low-accumulator genotypes in crops offers a promising alternative, this strategy may be more suitable in the long term and its success will depend on future detailed studies. On the other hand, despite the negative consequences that may result from the long-term use of biochar, there is evidence showing that it is effective in reducing Cd in soils, and thus an ideal short-term solution that can be applied across the national territory.